Characterizing quality and composition of beef derived from cattle fed steam-flaked corn diets with combinations of dry-rolled corn and dried distiller’s grains with solubles - Black, Patricia Lynne (Kansas State University, 2009)
A trial was conducted replacing portions of steam-flaked corn with either dry-rolled corn or dried distiller’s grains with solubles to evaluate effects on performance, carcass characteristics, carcass composition, meat color stability, and meat sensory attributes. Seven hundred crossbred yearling heifers (302 ± 65 kg initial BW) were used in a randomized complete block experiment with a 2 x 2 factorial arrangement of treatments. All diets contained steam-flaked corn (SFC), and factors consisted of the levels of dry-rolled corn (DRC; 0 or 25%) and dried corn distiller’s grains with solubles (DDGS; 0 or 25%). Results revealed no interactions between DRC and DDGS in terms of effects on feedlot performance, and only minor interactive effects were observed for carcass characteristics and meat quality attributes. Feedlot performance and carcass characteristics were not affected by the addition of DRC or DDGS (P > 0.05). Carcass composition and meat quality attributes were measured to determine if fat content of carcasses was altered by feeding DDGS. Diet had no significant effects, as carcasses from the four treatments contained similar amounts of separable portions of muscle, adipose, and bone; and similar percentages of protein, moisture, and ether extract. Compositions of both adipose and muscle tissue were evaluated to assess differences in fatty acid profile. Minimal effects were noted on the fatty acid profiles of the muscle and adipose tissue from cattle fed DDGS or DRC. Feeding cattle DDGS decreased alpha tocopherol (vitamin E) content of meat (P < 0.05). Meat quality attributes were largely unaffected by addition of DRC or DDGS to the diet, as retail color display life, lipid oxidation, sensory attributes, and heterocyclic amine concentrations were not different among treatments. Overall, DRC or DDGS can replace portions of SFC without negatively altering feedlot performance, carcass characteristics, meat composition, or meat quality attributes.
Keywords: Distiller's Grains; Steam-Flaked Corn; Finishing Cattle; Carcass Composition; Dry-Rolled Corn; Meat Quality; Agriculture, Animal Culture and Nutrition (0475)